Fauna Phylostomidae of the central region of the State of Rondônia, Brazil (Research, Society and Development, 2022)
Phylostomidae bats are mammals that live under a harmonious and intraspecific ecological relationship. In the central region of Rondônia, various species of bats colonize caves on the edge of bodies of water, mines and abandoned houses, hollow trees and normal and angled culverts along the axis of the highways. The versatility of many of these species is part of forest mitigation and pest control in agriculture. The objective of this work was to know the diversity and ecology of the Phylostomidae family in the municipalities of Ji-Paraná and Governador Jorge Teixeira in the state of Rondônia. The research was developed in two time frames 2007 – 2009, exploration of shelters; 2010 – 2021, response to notifications of hematophagous bat bites in captures with gillnets). The recognized diversity was sixteen species in three subfamilies of bats existing in the Amazon biome.